Theories and Modes of Climate-Smart Agriculture - Li, Bo, (Agronomist); Yin, Xiaogang; Wang, Quanhui; Chen, Fu, (Agricultural scientist); Zhang, Wejin (Singapore : World Scientific Publishing Co. Pte. Ltd., 2024)
"This unique compendium describes the development status and trends of international climate-smart agriculture, research methods and development strategies, monitoring, evaluation and extension, typical cases and their implications for the development of climate-smart agriculture in China. The useful reference text also comprehensively summarizes the relevant achievements and experiences obtained by the Climate-Smart Staple Crop Production Project, and highlights future policy suggestions and technical systems"--
Chapter 1. Introduction -- Chapter 2. Current status of international climate -- Chapter 3. International climate smart agriculture practice approach -- Chapter 5. International climate smart agriculture cases -- Chapter 6. Background of Chinas climate smart agricultural development -- Chapter 7. Practice and exploration of climate-smart wheat-rice production in China -- Chapter 8. Practice and exploration of wheat-maize production with climate-smart in China -- Chapter 9. Summary of China's climate smart agriculture mode experience.
Includes bibliographical references and index.
Keywords: Crops and climate -- China; Sustainable agriculture -- China; Vegetation and climate -- China